(untitled) (CIPEEX, 2025)
ABSTRACT: Contraception is a cost-effective strategy that allows men and women to plan the timing of their children’s arrival. The SUS (Brazilian Unified Health System) offers different methods, such as hormonal (oral and injectable), barrier (condoms and diaphragm), intrauterine devices (IUD), and definitive sterilization (tubal ligation and vasectomy). Within SUS, contraceptive methods are chosen according to the patient’s preference, who receives information during reproductive planning consultations in Primary Care. The Ministry of Health guides services through manuals and protocols. For contraceptive surgery (tubal ligation or vasectomy), it is necessary to meet legal requirements, sign a consent form, and wait 60 days before the procedure, ensuring time for reflection. Method efficacy is also an important criterion in the choice. Among injectables, medroxyprogesterone acetate and the combination of norethisterone enanthate + estradiol valerate are available. The choice of method should be free and informed, according to the patient’s reality and preference. It is important to highlight that condoms are the only method that, in addition to preventing pregnancy, also protect against Sexually Transmitted Infections (STIs). Contraception represents a fundamental advance in reproductive health, offering people the possibility to plan motherhood and fatherhood in a safe and conscious way. Among the available methods, internal and external condoms stand out as the main physical barriers to fertilization, which, in addition to preventing pregnancy, are the only ones that also protect against STIs. The contraceptive pill, one of the most widely used methods in the world, symbolizes a milestone in women’s autonomy. Composed of synthetic hormones similar to estrogen and progesterone, it prevents ovulation and modifies cervical mucus, although it has contraindications that must be assessed by a physician. Another alternative is the injectable hormonal contraceptive, administered monthly or quarterly, which works similarly to the pill but with greater practicality. Also hormonal, the subdermal implant is a long-term option: inserted under the skin of the upper arm, it continuously releases substances that prevent ovulation and hinder sperm from reaching the egg. Among non-hormonal methods, the Intrauterine Device (IUD) stands out, especially the copper IUD, which triggers an inflammatory reaction in the uterus capable of eliminating sperm. With long duration and high efficacy, it can remain effective for up to ten years without requiring continuous use or daily discipline. Finally, there are definitive methods: tubal ligation and vasectomy. Both are surgical procedures that interrupt the path of gametes, ensuring permanent efficacy. Precisely because of their irreversibility, these methods require professional follow-up, family planning sessions, and careful evaluation. Thus, the diversity of available options enables each individual or couple to choose the method most appropriate to their reality, always based on information, autonomy, and health care.